An Analysis of English Curriculum in The Village School - Syaepul Uyun, Aip; Ahsanul Arifin , Ryadh; Syarifah, Liah Siti (ETERNAL (English Teaching Journal), 2025)
The objective of this research is to give a brief description of an obstacles and issuesf English instruction in the school in village, and how the English curriculum in the village can be developed. This research was conducted in the Binar Ilmu Boarding School Cimenyan Bandung. Qualitative descriptive specific design was used in this study. Data were collected from interviews, observations and documentation. The research found that the major issue of English instruction in village are geographical condition, teacher qualification, student interest and lack of understanding of curriculum development.  On the other hand, it was also found that there are two stage of the process of English curriculum development, those are preparation, analysis and organization. Apart from these three stages, Teachers' and school management understanding of the curriculum development paradigm is an absolute factor that they must know before developing the curriculum. This measure has provided significant advantage to all parties, particularly school and teachers teaching English in village. Therefore, teaching English in village, need more effort and creativity.  So that they can easily develop their own curriculum in teaching English.